Phylogenetic Analysis Matrix from Borealodon osedax , a new stem mysticete (Mammalia, Cetacea) from the Oligocene of Washington State and implications for fossil whale-fall communities - B. K. Shipps; Carlos Mauricio Peredo; Nicholas D. Pyenson (2019)
Baleen whales (mysticetes) lack teeth as adults and instead filter feed using keratinous baleen plates. They do not echolocate with ultrasonic frequencies like toothed whales but are instead known for infrasonic acoustics. Both baleen and infrasonic hearing are separately considered key innovations linked to their gigantism, evolutionary success and ecological diversity. The earliest mysticetes had teeth, and the phylogenetic position of many so-called toothed mysticetes remains debated, including those belonging to the nominal taxonomic groups Llanocetidae, Mammalodontidae and Aetiocetidae. Here, we report a new stem mysticete, Borealodon osedax gen. et sp. nov, from the Oligocene of Washington State, USA. Borealodon preserves multi-cusped teeth with apical wear; microCT scans of the inner ear indicate that the minimum frequency hearing limit of Borealodon was similar to mammalodontids. Borealodon is not recovered within a monophyletic Mammalodontidae nor a monophyletic Aetiocetidae; instead, it represents an unnamed lineage of stem Mysticeti, adding to the diversity of stem mysticetes, especially in across the Rupelian–Chattian boundary. Furthermore, the presence of a putative chemosynthetic bivalve along with Osedax , a bone-boring annelid, found in association with the type specimen of Borealodon , offer more insights into the evolution of these deep-sea whale-fall communities.